Quality control of agricultural products (corn grain and sunflower seeds) criterion for the content of pesticide residues - Chervyakova, L.N.; Panchenko, T.P.; Adamenko, N.M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The method of determination of phosphorous acid and aluminum phosphite photometric method which allows to evaluate the mass fraction of active substances in the grain of corn and sunflower seeds, and gives the ability to control their content at the level of hygienic standards.